PENGARUH PERSEPSI DAN SIKAP GURU TERHADAP KESIAPAN GURU MATA PELAJARAN AKUNTANSI DALAM IMPLEMENTASI KTSP DI SMA NEGERI SE-KABUPATEN BLITAR - Prabowo, Andri Eko (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
The change of curriculum from KBK to KTSP expects more autonomous pupils and teachers, so it can improve studentsâ competency and teachersâ competency in teaching-learning process in the future. Every teachersâs perception, however, makes the implementation of KTSP different among each other because there are diversity in getting information, experiences, and fieldwork. It also occurs in teachersâ attitude because concerning to the KTSP socialization, culture which is various will make various teachersâ attitude toward the implementation of KTSP. So, the teachersâ attitude and perception leads to the different teachersâ readiness in implementation of KTSP. Therefore, this research has an objective to know the effect of teachersâ attitude and perception within implementation of KTSP. The research is conducted in state senior high schools in Biltar Regency on Februari â March 2008 by distributing closed-questionnaire. It uses path analysis with teachersâ attitude and perception as independent variable, while teachersâ readiness as dependent variable. After analyzing the data, the researcher gets correlation score 0.491. it means that the effect of teachersâ percetion and attitude within implementation of KTSP is strong with the percentage of it is 49.1%. it indicates that there are still many factors except those independent variables which influence the teachersâ readiness in implementing the KTSP. In conclusion, teachersâ perception and attitude has strong effect towards teachersâ readiness in implementations of KTSP.